Diseño de un producto turístico cultural para el desarrollo del turismo de la zona centro de Manabí. - Espinoza Navarrete, Gema M. (2018)
The research aims to design a cultural tourism product for tourism development in the central area of Manabi province, which will allow to implement and promote cultural tourism and facilitate the proper use of tourism resources. The research process consists of three phases. The first phase was aimed at the market study to determine the degree of interest and acceptance of the product, in addition to identifying the profile of the visitor to make way for the design of promotion and advertising strategies. In the second phase, the cultural tourism product was structured, which allowed integrating the tourist resources of greater interest and potential that are found in the Manabi area, seeking in this way the socioeconomic dynamism in the territory through tourism. In the third phase, the synergy of the cultural tourism product in the area was determined, for which an assessment of the benefits of the cultural product was made, based on the sustainability and involvement of the inhabitants. For the fulfillment of each of the aforementioned phases, several research methods were used, such as analytical-synthetic, documentary and inductive-deductive, in turn, various techniques and tools were used to obtain relevant information and develop the stages that integrated each research phase, thus fulfilling the fundamental purpose that consisted in the proposal of a cultural tourism product.